Potential of an ultra-high pressure-treated gluten-free mix as an improving ingredient in gluten-free breadmaking - SILVA, Gisela Benatti; QUEIROZ, Yasmin Carletto de; BARROS, Jefferson; CRISTIANINI, Marcelo; STEEL, Caroline (Food Science and Technology, 2024)
In the search for ingredients to improve the quality of gluten-free breads, a suspension of rice flour, cassava starch, and egg albumin (GF-Mix) was subjected to high pressure processing (HPP), to develop an ingredient capable of providing gluten-free breads of desirable quality. A central composite rotational design was followed, varying pressure (300–600 MPa), exposure time (5–10 min), and processing temperature (30–50°C). The samples were evaluated regarding pasting properties, instrumental color, and optical microscopy. The combination of high pressure and high temperature altered the pasting curves and reduced the parameters such as trough, final viscosity, and setback viscosity of the samples. An increase in the pasting temperatures was observed with the higher pressure and temperature conditions (600 MPa and 50°C) and intermediate processing times (4–8 min). Optical microscopy showed a loss of birefringence with increased pressure and temperature. The technological characteristics of the GF-Mix, processed through HPP at 600 MPa, 50°C, for 7.5 min, indicate a potential ingredient for gluten-free breadmaking, due to changes occurring in the starch leading to an ingredient with characteristics similar to a viscoelastic network.